ANALISIS STRATEGI GURU DALAM MEMBENTUK SIKAP SOSIAL SISWA SD NEGERI PERTIWI LAMGAROT - Fitriana; Nurmasyitah; Mislinawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the importance of developing students’ social attitudes in elementary schools through strategies implemented by teachers during the learning process. Social attitudes such as honesty, discipline, responsibility, politeness, caring, tolerance, and self-confidence need to be developed from an early age so that students are able to interact positively within the school and community environment. This study aimed to analyze teachers’ strategies in shaping students’ social attitudes at SD Negeri Pertiwi Lamgarot. The study employed a qualitative approach with a descriptive research design. The research subjects consisted of six classroom teachers from grades I to VI. Data were collected through observations and structured interviews. The data were analyzed through data reduction, data display, and conclusion drawing and verification. The findings showed that teachers’ strategies in shaping students’ social attitudes were implemented through modeling and habituation, rule enforcement, assigning tasks and responsibilities, and fostering politeness, caring, tolerance, and self-confidence. Teachers also applied educational rewards and sanctions, created a comfortable learning atmosphere, and provided motivation to students. The most dominant strategies used were modeling and habituation because they were considered effective in gradually and continuously shaping students’ social behavior in the school environment